In-Silico Investigation of Selected Phytochemicals as Potential Androgen Receptor Modulators: A Molecular Docking and ADMET Study - Esmaeil Belead Musa; Abdulaziz Sh. Suwaydan; Mhmoud Ali Zughdani; Aya Khaled Hadia; Duaa Mohammed Alyseer; Fatimah Alsanousi Bilhajjah; Samiran Sadhukhan (African Journal of Advanced Pure and Applied Sciences, 2026)
The Androgen Receptor (AR) is a fundamental therapeutic target for hormone-sensitive diseases, including prostate cancer. This study employed a computational workflow to evaluate the binding potential of five selected phytochemicals—Quercetin, Ursolic acid, β-sitosterol, Berberine, and Rutin—against the human AR (PDB ID: 2AMB). Ligand and receptor preparation were performed using Discovery Studio, while text editing and parameter adjustment were facilitated through Notepad++. Molecular docking was conducted using AutoDock Vina, and molecular visualization and interaction analysis were carried out with PyMOL. Docking results demonstrated that Quercetin and Berberine exhibited the most favorable binding energies of −8.8 kcal/mol and −8.7 kcal/mol, respectively, indicating strong binding affinity for the AR pocket. Evaluation of drug-likeness using Lipinski’s and Veber’s rules revealed that Quercetin and Berberine comply with pharmacokinetic criteria, whereas Ursolic acid, β-sitosterol, and Rutin showed multiple violations. ADMET predictions further identified Quercetin as possessing favorable oral absorption and metabolic profiles. Detailed molecular interaction analysis elucidated the key amino acid residues stabilizing the ligand within the AR binding pocket. These findings support and underscore supporting the identification of Quercetin as the most promising lead compound for AR modulation, providing a computational foundation for subsequent in vitro and in vivo investigations to validate Quercetin as a potential AR modulator.